Leadership, Motivation, and Discipline as Determinants of School Quality: A Study in Pekalongan Regency - Hidayah, Emi; Sumarno, Sumarno; Rasiman, Rasiman (LP. Ma'arif Janggan Magetan, 2025)
This study aims to examine the influence of school principal leadership, teacher work motivation, and teacher work discipline on school quality in SMP/MTs in the Tirto District, Pekalongan Regency. Using a quantitative approach, data were collected through questionnaires administered to 100 teachers from five schools. The findings reveal that all three independent variables principal leadership, teacher motivation, and teacher discipline positively and significantly influence school quality. Principal leadership contributes 60.5%, teacher motivation 43.4%, and teacher discipline 38.2% to the variation in school quality. Collectively, these factors account for 93.2% of the variance in school quality, underscoring the critical role of leadership, motivation, and discipline in shaping educational outcomes. These results emphasize that strong leadership fosters a shared vision and instructional support, while motivated and disciplined teachers enhance the consistency and effectiveness of learning processes. Therefore, strengthening school leadership practices, cultivating teacher motivation, and maintaining professional discipline are essential strategies for improving the overall quality of education in the Tirto District.